Extenuating lead toxicity in Chinese cabbage using organic acids: Comparative efficacy of acetic, citric, and tartaric acids - Rizwan, Muhammad; Riaz, Umair; Aziz, Humera; Anum, Wajiha; Rizwan, Muhammad; Murtaza, Ghulam; Yong, Jean Wan Hong; Chen, Hong (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
Lead (Pb) toxicity in the environment and plants has emerged as a significant global concern, primarily due to its entry into the human body through the food chain. Several physicochemical and biological techniques are being explored for Pb removal/immobilization. This study explored the efficacy of organic acids-citric acid (CA), acetic acid (AA), and tartaric acid (TA) in mitigating Pb toxicity in plants parts. The treatments included a control (CK, no acid treatment), citric acid (CA) at 0.25 mM (CA0.25) and 0.5 mM (CA0.5), tartaric acid (TA) at 100 mM (TA100) and 200 mM (TA200), and acetic acid (AA) at 100 mM (AA100) and 200 mM (AA200), each replicated in triplicate. Chinese cabbage (Brassica rapa) was used as the test crop. Our results revealed significant reductions in Pb concentrations in both plant parts (roots and leaves) as well as in soil following the addition of organic acid. Among the three acid treatments at different concentrations, tartaric acid (TA200) at 200 mM delivered the best results in reducing Pb accumulation in soil-plant system. It notably increased catalase activity (144 mu mol g(-1)), ascorbic acid (12,344 mg L-1), superoxide dismutase (178 U mg(-1) protein), and glutathione (98.0 mu g g(-1) FW), compared to citric and acetic acids treatments. Further, Pearson's correlation showed a strong negative relationship between Pb content and antioxidant activities, such as catalase, glutathione, and peroxidase (r > 0.90). This study revealed that the application of tartaric acid (TA), particularly at 200 mM through both exogenous and soil treatments, could be an effective strategy to minimize Pb accumulation in polluted areas.
Keywords: Phytoremediation; Soil chemistry; Metal toxicity; Biochar; Waste; Acids; HEAVY-METAL; CONTAMINATED SOIL; CADMIUM TOXICITY; ACCUMULATION; PLANTS; PB; CAPACITY; STRESS; CD; Environmental Sciences & Ecology; Toxicology